(untitled) (Research, Society and Development, 2020)
Objective: To narrate the benefits of birth in mother and baby water. In addition to describing necessary nursing care regarding water birth and discussing the importance of implementing water birth in the maternity wards. Method: An exploratory, descriptive, Literature Integrative Review (RIL) type study was conducted, which is a method that provides knowledge and results of studies in practice, with a broad methodological approach incorporating concepts, review of theories, evidence, and analysis of methodological problems. Result: The results achieved were the review of relevant articles that addressed case reports published between 2010 and 2020, benefits to nursing professionals and the strengthening of ties between patient, newborn and obstetric team. Conclusion: Therefore, water birth is among the safest maneuvers to perform humanized childbirth, as long as a good prenatal follow-up is performed, protecting the health of the mother and the baby, aiming at the best care. Another important factor is the follow-up by qualified and trained professionals, for this accomplishment and adjustments when necessary.